Controller Based Proxy for Handling NDP in OpenFlow Network - Sumadi, Fauzi Dwi Setiawan; Chandranegara, Didih Rizki (Universitas Muhammadiyah Malang, 2019)
A significant method should be deployed in OpenFlow environment for reducing the complexity during the implementation of IPv6 neighbor discovery protocol (NDP) in multicast manner. This paper was performed for deploying reactive-based application in controller’s northbound layer for handling as well as cutting the Neighbor solicitation packet’s journey. The application had a capability for storing each of the incoming Neighbor Solicitation (NS) and Neighbor Advertisement (NA) packet information. Therefore, the controller could reply the NS packet directly by using OFPT_PACKET_OUT message that contained the NA packet extracted from the reactive application. The experiment’s result showed that the proposed approach could reduce the NS response time up to 71% than the normal result produced by the traditional/learning switch application.